Exploring the Nexus of Environmental Awareness, Sustainable Development, and Modern Societal Trends - K. Shah, Umang (Digital Repository of Theses - SSBM Geneva, 2025)
Environmental awareness and sustainability are global priorities because of globally highlighted eco-related issues, resource scarcity, and socio-economic inequality. This study frames the relationship between environmental consciousness, sustainability, and contemporary partnerships within society, including corporate social responsibility, consumer patterns and rights, and political action. Due to global networks, such as the United Nations Sustainable Development Goals (SDGs), and national-level policies, particularly India's ban on plastic use, and the Green Skill Development Program, changes are globally systemic. Corporate sustainability is no longer a choice for business, but essential; it is a strategic imperative - even businesses now account for Environmental, Social, and Governance (ESG) as they maximize long-term profitability and risk mitigation towards positive social outcome indicators. Despite the commitment towards sustainability, businesses take advantage of the growing innovation, blockchain in supply chains and energy efficiency in artificial intelligence (AI). Businesses with sustainable transformation expect to face regulatory issues, misleading environmental claims, and operating costs. Customer behavior remains a fundamental determinant of market trends, with a growing preference for social and sustainable consumption. Research shows that a large contingent of consumers worldwide prefer brands that engage in sustainable product production processes, thus creating a case for brands to commit to sustainability by engaging in green marketing, eco-labeling, and circular economies. However, several challenges such as the price of sustainable goods, misperception of sustainable products, and lack of access to these developments can become barriers to employing sustainable practices on mass consumption levels. Subsequently, tackling these barriers requires a concerted effort by policymakers, businesses, and advocacy organizations to educate consumers, increase accessibility and availability to sustainably and socially sound goods, in addition to lowering the price of these goods. Political discourse represents sustainability concerns in the public realm due to international sustainability agreements such as the Paris Climate Accord and national agreements such as India's National Action Plan on Climate Change (NAPCC). Grassroots movements and online activism have heightened public demand for stronger environmental policies and commitments, which continue to push government and corporate behavior to adopt more verifiable sustainable behavior. This study offers implications on the barriers and drivers of sustainability behaviors and offers several actionable tips to policymakers, businesses, and consumers. This research reinforces the collaborative effort required to foster a sustainable and resilient future by enhancing interdisciplinary collaboration, digital advancements, and institutional frameworks. The results have enhanced understanding of sustainability behaviors and factors contributing to sustainable practices in global societies.